Association of disease activity with programmed cell death 1 and its ligand programmed cell death ligand 1 expressions in lupus patients - Eman Eissa; Rania Kandil; Nehal El-Ghobashy; Walaa Abdelfattah; Zainab Hammouda; Sara Medhat Gadelsayed; Faten Bayoumi (Indian Journal of Rheumatology)
Background: Programmed cell death 1(PD-1)/programmed cell death ligand 1 (PD-L1) pathway is an immune checkpoint implicated in immune tolerance and involved in the pathogenesis of several autoimmune diseases. Systemic lupus erythematosus (SLE) is an autoimmune disease with multiple immune dysregulation. This study aimed to determine PD-1 and PD-L1 expressed levels on both CD3 T and CD19 B lymphocytes in SLE patients compared to healthy donors and their associations with the clinical data and disease activity of those patients. Patients and Methods: A total of 25 healthy donors and 80 SLE patients were involved in the study. PD-1 and PD-L1 expressed levels on each of CD3 T and CD19 B lymphocytes were determined in the peripheral blood (PB) using flow cytometry. Results: The expressed levels of PD-1 and PD-L1 on both CD3 T and CD19 B lymphocytes were significantly higher in PB of SLE group than that of controls (P = 0.01, P = 0.001, P = 0.009, and P = 0.001). Significant positive associations were found between PD-1 and PD-L1 expressions on both CD3 T and CD19 B lymphocytes with disease activity in SLE group (P < 0.05). Conclusion: PD-1 and its ligand PD-L1 could have a role as regulators for immune activation in patients with SLE.